Benin : Report on the Observance of Standards and Codes-Fiscal Transparency Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This report evaluates the Observance of Standards and Codes on the Fiscal Transparency Module for Benin. The assessment reveals that significant progress has been made in improving fiscal transparency in Benin in recent years. The budget execution accounts for fiscal year 1998 were submitted to parliament at end-1999 for the first time in more than 30 years. Fiscal transparency has improved in a number of other areas with the introduction of new budget and account classifications. Program budgets have been introduced since fiscal year 2000, and a computer-based expenditure management system has been implemented.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet